Innovative approaches to integrating gender into conventional maize breeding : lessons from the Seed Production Technology for Africa project - Voss, Rachel C.; Cairns, Jill E.; Olsen, Michael; Muteti, Francisca Ndinda; Magambo, George; Hamadziripi, Esnath; Ligeyo, Dickson; Mashingaidze, Kingstone; Collinson, Sarah; Wanderi, Susan; Woyengo, Vincent (Frontiers Media, 2023)
The integration of gender concerns in crop breeding programs aims to improve the suitability and appeal of new varieties to both women and men, in response to concerns about unequal adoption of improved seed. However, few conventional breeding programs have sought to center social inclusion concerns. This community case study documents efforts to integrate gender into the maize-focused Seed Production Technology for Africa (SPTA) project using innovation history analysis drawing on project documents and the authors’ experiences. These efforts included deliberate exploration of potential gendered impacts of project technologies and innovations in the project’s approach to variety evaluation, culminating in the use of decentralized on-farm trials using the tricot approach. Through this case study, we illustrate the power of active and respectful collaborations between breeders and social scientists, spurred by donor mandates to address gender and social inclusion. Gender integration in this case was further facilitated by open-minded project leaders and allocation of funding for gender research. SPTA proved to be fertile ground for experimentation and interdisciplinary collaboration around gender and maize breeding, and has provided proof of concept for larger breeding projects seeking to integrate gender considerations.